The Exploration Potency of Bioactive Compounds of Leaves Extract Nipah (Nypa Fruticans Wurmb) from The Coast of West Aceh as Antioxidant - Mohamad Gazali; Hayatun Nufus; Nurjanah Nurjanah; Zuriat Zuriat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
West Aceh Region has Nypa fruticans mangrove community distributed almost ±100 Ha. N.  fruticans  leaves have been used as traditional cigarette paper. The objective of this study was to explore bioactive compound of  N. fruticans from the coast of West Aceh as antioxidant. The extraction used 3 solvents including methanol (polar), etyl acetate (semi polar), and n-hexane (non polar). The result showed the methanol extract contained  bioactive compound content such as phenolic, flavonoid, tannin, saponin, and steroid while the etyl acetate extract comprised phenolic, tannin, and steroid. Moreover, n-hexane extract only had steroid compound. The result of antioxidant activit assay showed etyl acetate extract had IC50 value 8.81 µg/mL, methanol extract had IC50 value 9.31 µg/mL and n-hexane extract was 238.47 µg/mL with ascorbic acid as positive control. It is indicated the presence of phenolic, flavonoid, tannin, and saponin in the ethyl acetate extract play the role as antioxidant.